Patient Education Is Associated with Reduced Delay to Presentation for Management of Ischemic Priapism: A Retrospective Review of 123 Men. Issue 2 (6th January 2021) - Dutta, Rahul; Matz, Ethan L.; Overholt, Tyler L.; Anderson, William B.; Deebel, Nicholas A.; Cowper, Matthew; Terlecki, Ryan P.; Scarberry, Kyle A.
ABSTRACT: Background: Adverse outcomes secondary to ischemic priapism (IP) are associated with time to presentation and management. Aim: To characterize patterns in presentation delay as a function of etiology and patient education regarding IP risk. Methods: Following institutional review board approval, charts of IP patients presenting to our institution from 2010 to 2020 were reviewed. One episode of IP per patient was included for analysis. Outcomes: Priapism duration in patients presenting with IP. RESULTS: We identified 123 unique patients with IP. Common etiologies included erectogenic intracavernosal injection (24%), trazodone (16%), and other psychiatric medications (16%). Patients with sickle cell anemia or trait and intracavernosal injection–related IP presented sooner than idiopathic cases and those from psychiatric medication ( P < .001). Etiology and provider education on IP risk were associated with presentation ≥ 24 hours. Upon multivariate analysis, only a lack of provider education was independently associated with presentation ≥ 24 hours. Clinical Implications: Men who received provider-based education on the risk of IP associated with their condition or medication regimen were more likely to seek prompt medical attention for IP and, therefore, less likely to require surgery. Strengths & Limitations: This manuscript represents one of the largest series on priapism, an area of urologic practice in need of more evidence-based guidance. The numbers are not inflated by including multiple episodes per patient, and the data collected include etiology, time to presentation, and treatment. Limitations include a retrospective chart review study design at a single institution. CONCLUSION: Educational initiatives on the risk of IP associated with particular disease states and medications should target at-risk individuals, as well as prescribers of medications associated with IP.